Early detection of euglycemic ketoacidosis during thoracic surgery associated with empagliflozin in a patient with type 2 diabetes: A case report. Issue 4 (26th August 2020) - Kitahara, Chie; Morita, Shuhei; Kishimoto, Shohei; Matsuno, Shohei; Uraki, Shinsuke; Takeshima, Ken; Furukawa, Yasushi; Inaba, Hidefumi; Iwakura, Hiroshi; Ariyasu, Hiroyuki; Furuta, Hiroto; Nishi, Masahiro; et al.
Abstract: We report the first case of intraoperatively detected euglycemic diabetic ketoacidosis (DKA) associated with sodium–glucose cotransporter 2 inhibitors during thoracic surgery. A 59‐year‐old man had a 12‐year history of type 2 diabetes mellitus treated with insulin and empagliflozin. The patient developed bacterial empyema and was initiated with antibiotics at a local hospital. Owing to the persistence of his symptoms, he was transferred to our hospital after the medication of empagliflozin the day before surgery. After overnight fasting, the patient underwent thoracoscopic debridement and intrathoracic lavage surgery. During this surgery, he was noted to have euglycemic ketosis and acidosis, and diagnosed as euglycemic DKA. Immediately after the consultation in our department, the patient underwent treatment for DKA. He awoke from anesthesia normally and showed no symptoms of DKA. DKA gradually resolved over the next 24 h. Early identification and management are critical for rapid recovery from perioperative euglycemic DKA associated with sodium–glucose cotransporter 2 inhibitors, especially during thoracic surgery. Abstract : Surgery is a known risk factor of diabetic ketoacidosis (DKA) for patients with an insufficient withdrawal period of sodium–glucose cotransporter 2 (SGLT2) inhibitors. Although there are the cases of DKA associated with sodium–glucose cotransporter 2 inhibitors after surgery, we report the first case of euglycemic DKA associated with empagliflozin detected during thoracic surgery. Awareness of the risk of euglycemic DKA is critical for early identification, management and even prevention when patients are treated with sodium–glucose cotransporter 2 inhibitors.